William Somerset Maugham and the Nobel Prize - Paulus Tiozzo (Current Swedish Archaeology, 2021)
This article provides an analysis of the Swedish reception and Nobel Prize nominations of William Somerset Maugham. Its purpose is firstly to present a largely unknown aspect of the reception of his work through an assessment of reviews published in Swedish newspapers from 1908 to 1965. These years cover Maugham’s first mention in a Swedish context until the year of his death. Secondly, it will offer an explanation as to why he ultimately did not receive the Nobel Prize, although he was held in high esteem by members of the Swedish Academy, who wrote several reviews of his work. It is probable that this was because of his fame and success rather than for any aesthetic, moral or even political reasons. All these conclusions are derived from an analysis of original documents, including letters and protocols from the archives of the Swedish Academy. The article begins with a brief description of the criteria for the Nobel Prize in Literature and how they were applied at the time of Maugham’s nominations, followed by a discussion of his reception by Swedish critics; the final section concerns the Nobel Prize nominations themselves.